Room temperature uniaxial magnetic anisotropy induced by Fe-islands in the InSe semiconductor van der Waals crystal - Moro, Fabrizio; Bhuiyan, Mahabub A.; Kudrynskyi, Zakhar R.; Puttock, Robert; Kazakova, Olga; Makarovsky, Oleg; Fay, Michael; Parmenter, Christopher D.J.; Kovalyuk, Zakhar D.; Fielding, Alistair John; Kern, Michal; van Slageren, Joris; et al. (Wiley-VCH Verlag, 2018)
The controlled manipulation of the spin and charge of electrons in a semiconductor has the potential to create new routes to digital electronics beyond Moore’s law, spintronics, and quantum detection and imaging for sensing applications. These technologies require a shift from traditional semiconducting and magnetic nanostructured materials. Here, a new material system is reported, which comprises the InSe semiconductor van der Waals crystal that embeds ferromagnetic Fe-islands. In contrast to many traditional semiconductors, the electronic properties of InSe are largely preserved after the incorporation of Fe. Also, this system exhibits ferromagnetic resonances and a large uniaxial magnetic anisotropy at room temperature, offering opportunities for the development of functional devices that integrate magnetic and semiconducting properties within the same material system.